Implementation of a pharmacogenetic management service for postmyocardial infarction care in a community pharmacy. (August 2015) - Bright, DR; Kisor, DF; Smith, A; Conaway, M; Yu, M
Aim: The purpose of this study was to pilot a multisite, proof-of-concept model where community pharmacists could engage patients and physicians to provide pharmacogenetic (PGt) testing and clinical decision support.Patients & methods : Patients with history of acute myocardial infarction and percutaneous coronary intervention with no prior history of CYP2C19 testing.Results : Four community pharmacies provided pharmacogenetic testing and medication therapy management services to 30 patients, resulting in eight recommendations for antiplatelet therapy adjustment.Conclusion : Pharmacists involved in the study were able to facilitate antiplatelet therapy adjustments based on PGt data regardless of baseline antiplatelet drug selection. Whereas prior literature largely revolved around PGt management in the inpatient setting, this project supports the involvement of the community pharmacist in making PGt-based recommendations.